TINJAUAN PENYIMPANAN ARSIP DINAMIS DI PENGADILAN TINGGI AGAMA BANDUNG - Dewi Maryunizah; Ary Yanuarti; Silvi Triandini (SECAD, 2025)
This study aims to find out about the implementation of dynamic archive storage at the Bandung High Religious Court. The method used in this study is a quantitative descriptive method, namely describing, researching, and explaining something that is studied as it is, and drawing conclusions from phenomena that can be observed using numbers, the number of respondents is 32 people at the Bandung High Religious Court. Based on the results using data tabulation and where the data is obtained from respondents' answers to the questionnaire that the researcher distributed. With a result of 3,981 and it is considered